The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/978-3-030-16892-6_7
|View full text |Cite
|
Sign up to set email alerts
|

What Do Pāsifika Students in New Zealand Value Most for Their Mathematics Learning?

Abstract: Achieving equity for all mathematical learners is an urgent challenge for educators. Within New Zealand, Pāsifika students are at a much greater risk of underachievement than students from other ethnic groups (Caygill et al. in TIMSS 2015: New Zealand Year 5 Maths results. Comparative Education Research Unit, Ministry of Education, Wellington, 2016a; Caygill et al. in TIMSS 2015: New Zealand Year 9 Maths results. Comparative Education Research Unit, Ministry of Education, Wellington, 2016b). In this chapter, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
2
24
1
Order By: Relevance
“…The low ranking of utility as a mathematics educational value is surprising, given that in previous studies (e.g., Hill, 2017;Hill et al, 2019;Ö sterling & Andersson, 2013;Seah & Barkatas, 2014;Zhang et al, 2016) across different cultural contexts, students have frequently ranked utility as an important value. Analysis of the student responses highlights that this finding may be indicative of the mathematics tasks and contexts that Pāsifika students experience within schooling.…”
Section: New Zealandmentioning
confidence: 90%
“…The low ranking of utility as a mathematics educational value is surprising, given that in previous studies (e.g., Hill, 2017;Hill et al, 2019;Ö sterling & Andersson, 2013;Seah & Barkatas, 2014;Zhang et al, 2016) across different cultural contexts, students have frequently ranked utility as an important value. Analysis of the student responses highlights that this finding may be indicative of the mathematics tasks and contexts that Pāsifika students experience within schooling.…”
Section: New Zealandmentioning
confidence: 90%
“…For these researchers, there is an agreement that values reflect teachers' approaches. More than that, sharing their views with Hill et al (2019), "when values were acknowledged in the mathematics classroom, relationships were strengthened, students' cultural identities were affirmed, students became more engaged, and, ultimately, mathematics learning was enhanced." In any case, the transference of values, as considered by Dede et al (2021), or alternatively the alignment of values, are of importance and interest to be investigated.…”
Section: Ecnu Review Of Education 4(2)mentioning
confidence: 99%
“…Clearly, both sets of values are underpinned by those of a collectivism society's and strongly focused on the wellbeing of the collective as a whole. In our recent research, we showed that students named family, respect, and collectivism as particularly important educational values they drew on as they engaged in mathematics in classrooms (Anthony, 2013;Hill et al, 2019;Hunter, 2021).…”
Section: Culturally Sustaining Mathematics Pedagogymentioning
confidence: 99%